Frictional resistance of contemporary orthodontics archwires and brackets:in vitro study - Faiza Imtiaz, Syed Shah Faisal, Syed Sheeraz Hussain Anum Mahmood, Amna Farrukh, Syeda Bisma Naseem, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Frictional resistance between orthodontic archwires and brackets significantly affects toothmovement efficiency during orthodontic treatment. This in vitro study aimed to evaluate the frictional resistance of contemporary